Role of CdSe and CdSe@ZnS quantum dots interlayers conjugated in inverted polymer solar cells - Park, Young Jae; Lee, Kyu Seung; Lim, Guh Hwan; Seo, Hae Woon; Kim, Sang Wook; Kim, Minju; Yi, Yeonjin; Lee, Hong Seok; Son, Dong Ick (Organic Electronics, 2020)
We demonstrate the use of CdSe quantum dots (QDs) as an interlayer for improving photovoltaic performance in the inverted polymer solar cells (iPSCs). The conjugation of CdSe and CdSe@ZnS core@shell QDs between polyethylenimine ethoxylated (PEIE) polymer and PTB7:PC71BM blended layer played an important role in increasing the short circuit current density by Förster resonance energy transfer (FRET) and efficient charge transport. The drastic mutual photoluminescence quenching suggests that the photon energy absorbed by PTB7:PC71BM are effectively transferred to the QDs. The PTB7:PC71BM based iPSCs with the CdSe QDs interlayer exhibits higher power conversion efficiency of 8.13%, which is 13.4% higher than that of the control device. The iPSCs with CdSe@ZnS QDs interlayer showed relatively lower PCE of 7.31%, which could be due to an increase in carrier recombination inside QDs by relatively high energy level of ZnS shell. As a consequence, the enhanced photovoltaic performance of iPSCs with CdSe QDs interlayer can be attributed to an effective charge transport and an increase in the overall photocurrent by FRET.
Keywords: Cdse; Energy level alignment; Inverted polymer solar cells; Photoluminescence quenching; Photovoltaic performance; Polyethylenimine ethoxylated; Power conversion efficiencies; Resonance energy transfer; Carrier transport; CdSe; Energy level alignment; Inverted polymer solar cells; Quantum dots; Resonance energy transfer